Good Corporate Governance, Stakeholders, and Sustainability Report Disclosure - Sheila Najla Syahirah; Harry Suharman; Dede Abdul Hasyir; Jumadil Saputra (UIN Sunan Gunung Djati, 2023)
Indonesia currently lacks a mandatory framework for sustainability reporting, with the existing reporting requirements focusing on Corporate Social Responsibility (CSR) reports rather than comprehensive sustainability reporting. This situation has resulted in a significant gap in the disclosure of sustainability reports, as organizations often merely comply with CSR reporting obligations, neglecting broader sustainability considerations. In 2020, challenges in sustainability reporting were evident, particularly in the environmental, agrarian, and energy sectors. The Indonesian Forum for the Environment highlighted issues such as the overexploitation of energy resources for corporate profits and potential biases from the government in supporting energy and manufacturing markets, posing threats to sustainability reporting. This study investigates the influence of Good Corporate Governance (GCG) and stakeholder pressure on sustainability report disclosure. Utilizing a quantitative approach, the research focused on companies listed on the Indonesia Stock Exchange (BEI) operating in the energy, raw materials, industry, and infrastructure sectors, specifically those actively publishing sustainability reports. The data, extracted from sustainability reports available on the BEI website, underwent statistical multiple regression analysis. The findings reveal a significant positive impact of both good corporate governance and stakeholder pressure on sustainability report disclosure, accounting for 77.5%. The implications suggest that social pressure and GCG practices contribute to enhanced sustainability reporting, urging the government to establish more stringent regulations. Future research recommendations include expanding the sample size and incorporating additional variables.